Analisis Proses Pembentukan Kebijakan Publik: Studi Kasus Program Beasiswa Karawang Cerdas Tahun 2020 - Irvan Sudirman (Epistemik: Indonesian Journal of Social and Political Science, 2021)
This research aims to find out the process of policy formulation of Karawang Cerdas scholarship held in 2020 by the local government of Karawang Regency. The theory used in this study is the theory of public policy formation process by William N Dunn. The data collection techniques used in this study is observation and interview techniques. Meanwhile, to analyze the data used the qualitative-descriptive approach. The results of this study showed is conformity between the teory of public policy formation process put forward by William N. Dunn and the process of public policy formation of Karawang Cerdas program in 2020. Nevertheless, the results of this study also showed that there are still a number of problems in the process of public policy formation.